Effect of Different Pre-treatments and Frying Process on Proximate, Some Essential Minerals, and Anti-nutritional Factors of Taro Found in Birjung, Nepal - Sharma, Shristi Poudel; Thagunna, Bishal; Baral, Rosy; Baral, Rashmi; Khadka, Deepa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Taro corms (Colocasia Esculenta), also called pindalu in Nepalese society are exposed to different pretreatment such as boiling in plain water at 100ºC for 7min, boiling in 1.2% salt solution at 100ºC for 7min, boiling in 5% citric acid100ºC for 7min and frying was investigated for proximate, antinutritional and mineral content. The proximate composition of raw taro corms was found to be moisture 60.82%, crude fat 0.96%, crude protein 9.69%, total ash 3.77%, crude fiber 3.49% and carbohydrate 52.0%. Macro nutrients such as Potassium, Calcium, Phosphorous, and Sodium were found to be 620.55 mg/100g, 150.12 mg/100g, 53.72 mg/100g, and 36.62 mg/100g, respectively. Antinutritional factors of raw taro corms analyzed in this study were oxalate-280.98±0.49 mg/100g, phytate-84.90±0.74 mg/100g and tannin-47.67±0.11 mg/100g. Potassium was the most abundant macro mineral (620.55mg/100g) in the unprocessed taro corms. The effect of pretreatments and frying on calcium showed significant decrease. When compared with raw taro corms, pretreatments and frying process resulted in a significant increase in phosphorous and sodium content. Antinutritional factors were significantly reduced by the pre-treatments, and frying method appears to be more effective in reducing phytate and tannin, whereas boiling in 5% salt solution for oxalate content.